2015
DOI: 10.1002/er.3280
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stress simulation and chemical compatibility of glass composite seals with YSZ for solid oxide fuel cells

Abstract: The selection of the components is important for the solid oxide fuel cells (SOFC) in order to address the sealing issues. In the present investigation, the glass composite seals have been prepared by mixing the different glass compositions in fixed ratio and then ball milling for 5 h without using any unreactive particle in glass matrix. The chemical compatibility of the prepared glass composites with the solid electrolyte yttria stabilized zirconia (YSZ) has been studied using the scanning electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…They found that the initial bonded compliant seal design appears to function quite well by accommodating the mismatch thermal strains as elastic and plastic strains within the sealing foil. Gurbinder Kaur et al studied the thermal stress at the interfaces of electrolyte and seven glass composites seals.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the initial bonded compliant seal design appears to function quite well by accommodating the mismatch thermal strains as elastic and plastic strains within the sealing foil. Gurbinder Kaur et al studied the thermal stress at the interfaces of electrolyte and seven glass composites seals.…”
Section: Introductionmentioning
confidence: 99%